2021
DOI: 10.1002/cbic.202100490
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Enzymatic Activity by Modulating the Oligomerization State via Chemical Rescue and Optical Control

Abstract: Selective switching of enzymatic activity has been a longstanding goal in synthetic biology. Drastic changes in activity upon mutational manipulation of the oligomerization state of enzymes have frequently been reported in the literature, but scarcely exploited for switching. Using geranylgeranylglyceryl phosphate synthase as a model, we demonstrate that catalytic activity can be efficiently controlled by exogenous modulation of the association state. We introduced a lysine-to-cysteine mutation, leading to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Interestingly, it has been also reported that oligomerization of enzymes modulates their activities ( Kropp et al, 2022 ). We showed here that CypB dimer formation was fully required to complement the defective phenotype of Brucella Δc ypAB mutant in stress survival, intracellular adaptation, and virulence in mice but not required for the in vitro PPIase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been also reported that oligomerization of enzymes modulates their activities ( Kropp et al, 2022 ). We showed here that CypB dimer formation was fully required to complement the defective phenotype of Brucella Δc ypAB mutant in stress survival, intracellular adaptation, and virulence in mice but not required for the in vitro PPIase activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach suffers from low selectivity and versatility. These problems have been overcome by genetic code expansion, which uses the reprogramming of a stop codon to incorporate ncAAs at practically any desired position of a protein of interest. In this respect, photoxenoprotein engineering has enabled photocontrol of protein functions including modulation of enzyme activity and allostery, protein binding affinities, protein localization, and protein assembly and multimerization. …”
Section: Introductionmentioning
confidence: 99%